(3OjhGf HGeNQeIs - (3YeQ Hf YHO Gddg HGeNQeI GdgLQGfj GdTjHGfj GdMVQej,J (B952 (3g` s ((3GdSjO YHOGddg Hf eMeO Hf Rjf GdMHTj s)
(3ChdgG (B:s
(3GdMeO ddg GdSHjd Ydi bdhH GdYGQajf eYQaJg hMceg GdHGA(B: (3fGUQ Cjf GdPj UGHc YSi Gddg jUjHg Cjf Pj LqQYc ef OhM bQba RHjHg s
(3BNQgG (B:s
(3aj bGajI GdHGA drbJfGUj GdHhGOj GdHGOjGJ GdfhGjg Pj JhGajc ef ZjQ ELJgGO Ch SYGjg s
(3GdYfGhjf ecJhHI HGdMeQI hHGdfSNI JeRjbs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B35 s
Keywords: (3GdCOHs